2015
DOI: 10.1111/spol.12189
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Enablers to Safeguarding Children and Adults within a Disability Services Context: Insights from an Australian Delphi Study

Abstract: Research conducted in the 1990s revealed the tragic irony that exposure to the disability support system, and particularly to its institutional forms, was a major risk factor related to the neglect and abuse of children and adults with a disability. Subsequently, a range of policies have been introduced to minimize risk. However, recurring events of abuse and neglect in the disability services sector in high and middle income countries demonstrate that processes geared to safeguard children and adults with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Other barriers included a lack of inter-professional collaboration and expert consultation, inconsistent approaches to investigations, delayed reporting of abuse, delayed investigations, biased and leading questioning of victims by untrained professionals, lack of time to conduct a thorough investigation and lack of resources (Ahlgrim-Delzell & Dudley, 2001;Fyson & Kitson, 2012;Ottmann et al, 2017;Ramsey-Klawsnik & Teaster, 2012;Zuckerman et al, 1986). Fyson and Kitson (2012)…”
Section: Barriers To Detecting Abusementioning
confidence: 99%
“…Other barriers included a lack of inter-professional collaboration and expert consultation, inconsistent approaches to investigations, delayed reporting of abuse, delayed investigations, biased and leading questioning of victims by untrained professionals, lack of time to conduct a thorough investigation and lack of resources (Ahlgrim-Delzell & Dudley, 2001;Fyson & Kitson, 2012;Ottmann et al, 2017;Ramsey-Klawsnik & Teaster, 2012;Zuckerman et al, 1986). Fyson and Kitson (2012)…”
Section: Barriers To Detecting Abusementioning
confidence: 99%
“…Multiple studies in high income countries have shown very high prevalence of physical, sexual or partner violence affecting people with disability (Hughes et al, 2012). In Australia, people with intellectual or psychological disabilities and those living in congregate care face particularly high risks (Araten-Bergman et al, 2017; Ottmann et al, 2017). People with cognitive or psychological impairments are three times as likely as people without disability to have experienced violence in the last 12 months (CRE-DH, 2021).…”
Section: Prevalence and Antecedents Of Abuse And Neglectmentioning
confidence: 99%
“…Such harms continue to be underpinned by complex, convergent factors, including ableist community attitudes; segregated living and working arrangements; poorly designed and enforced regulation; and barriers to change within organizations (Royal Commission, 2020). Antecedents of abuse and neglect have been explored through a relatively small body of scholarship, which has identified systemic basis of risks, which arise from the isolation associated with impairment; unequal power relations between people with disability and caregivers in formal services; tolerance of inequality; and normalization of harmful practices (Laing, 2017; Ottmann et al, 2017). Charlesworth et al (2020) implicate markets, noting that providers have responded to intensified competition and financial pressures in ways that compromise quality and safety.…”
Section: Prevalence and Antecedents Of Abuse And Neglectmentioning
confidence: 99%
See 2 more Smart Citations